Dark energy: theory and observations - Amendola, Luca; Tsujikawa, Shinji (Cambridge University Press, 2010)
"Dark energy, the mysterious cause of the accelerating expansion of the Universe, is one of the most important fields of research in astrophysics and cosmology today. Introducing the theoretical ideas, observational methods and results, this textbook is ideally suited to graduate courses on dark energy, and will also supplement advanced cosmology courses. Providing a thorough introduction to this exciting field, the textbook covers the cosmological constant, quintessence, k-essence, perfect fluid models, extradimensional models, and modified gravity. Observational research is reviewed, from the cosmic microwave background to baryon acoustic oscillations, weak lensing, and cluster abundances. Every chapter ends with problems, with full solutions provided, and any calculations are worked through step-by-step. "--
Literaturverz. S. 457 - 484. - Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Lehrbuch; Dunkle Energie